Radiology Illustrated: Gynecologic Imaging - Kim, Seung Hyup.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Radiology Illustrated: Gynecologic Imaging is an up-to-date, image-oriented reference in the style of a teaching file that has been designed specifically to be of value in clinical practice. Individual chapters focus on the various imaging techniques, normal variants and congenital anomalies, and the full range of pathology. Each chapter starts with a concise overview, and abundant examples of the imaging findings are then presented. In this second edition, the range and quality of the illustrations have been enhanced, and image quality is excellent throughout. Many schematic drawings have been added to help readers memorize characteristic imaging findings through pattern recognition. The organization of chapters by disease entity will enable readers quickly to find the information they seek. Besides serving as an outstanding aid to differential diagnosis, this book will provide a user-friendly review tool for certification or recertification in radiology.
US and transvaginal US: techniques, normal findings, and variations -- Gynecologic CT and MR imaging -- Variations and congenital anomalies of the female genital tract -- Uterine myoma -- Uterine adenomyosis -- Uterine cervical carcinoma -- Endometrial carcinoma -- Miscellaneous tumors of the uterus -- Posttreatment changes and recurrence of uterine malignancies -- Gestational trophoblastic diseases -- Miscellaneous lesions of the uterus -- Ovarian cysts and cystic diseases -- Ovarian tumors -- Epithelial tumors of the ovary -- Germ cell tumors of the ovary -- Sex cord-stromal tumors of the ovary -- Miscellaneous tumors of the ovary and adnexa -- Endometriosis -- Ovarian torsion -- Pelvic inflammatory disease and tubo-ovarian abscess -- Ectopic pregnancy -- The vagina and vulva -- Vascular diseases of the female pelvis -- Pediatric gynecologic diseases -- Nongynecologic lesions mimicking gynecologic diseases -- Hysterosalpingography -- Sonohysterography -- Gynecologic nonvascular interventions -- Gynecologic vascular interventions.
Keywords: Medicine; Gynecology; Radiology, Medical; Medicine & Public Health; Imaging / Radiology; Gynecology